The Application of Al-Ijarah Muntahiya Bi al tamlik (Financial Lease With Purchase Option) As a Financing Solution in the Sharia Non-Bank Finance Industry - Bustami Bustami (AFEBI Islamic Finance and Economic Review, 2017)
To avoid buying and selling through installment (credit) that does not fall in buying and selling that contains the element of riba (that is not allowed by sharia), buying and selling through credit or bai’ al taqsit} is able to be implemented by using a pact of selling and leasing through the financing principle of Al-Ijarah Muntahiya Bi al Tamlik (Financial Lease With Purchase Option). The application of the Al-Ijarah Muntahiya Bi al Tamlik is more advantageous than the al-Murabahah pact and the interest system. Other than that it reflects the presence of the principles of justice and togetherness between the capital owner party (shahib al mal) with those that need financing.Keywords: Al-Ijarah Muntahiya Bi al tamlik, Bai’ al taqsîth, Justice, Togetherness